Sanctions against Russia: a new financial and economic reality? - I. N. Timofeev (Ибероамериканские тетради)
Every conflict sooner or later ends in peace. This is the conventional wisdom that can often be heard from those who, in the current “tsunami” of sanctions and confrontation with the West, try to find hope for a return to “normality”. For the most part, sanctions against Russia will not be lifted even if there is a ceasefire in Ukraine and the conflict is resolved. There will be no return to “pre-February normality”. Instead of remembering the lost past, the focus will have to be on creating a new future in which sanctions imposed by the West will remain a constant variable.